Probabilistic model for hydrate and wax risk assessment in oil and gas pipelines - Xu, Hongfei; Khan, Faisal; Jung, Seungho; Wang, Qingsheng (Process Safety and Environmental Protection, 2023)
Hydrates and wax are common hazards for oil and gas pipelines. The formation of hydrates and wax can lead to pipeline blockage, which may cause accidents incurring significant assets, safety, and environmental losses. The current study aims to develop a risk-based flow assurance model for hydrates and wax. The probabilistic models are developed to assess the likelihood of hydrate formation, hydrate blockage, and wax blockage. The proposed models use thermo-hydraulic data to estimate the probability of pipeline blockage hazards. The developed models are tested against the published studies and lab data. Application of the models is demonstrated using case studies. The models would help develop and implement pipeline design and intervention strategies to ensure a safer continued operation pipeline system.
Keywords: current; Flow assurance; Hydrate; Hydrate formation; Oil-and-Gas pipelines; Pipeline blockages; Probabilistic models; Risk-based; Risks assessments; Wax blockage; Flow Assurance; Hydrate; Risk Assessment; Wax Blockage